The Dual Transition of Electrical Switchgear: Navigating SF6 Alternatives and the Rise of Predictive Maintenance - Alhijazi, Ayman; Diab, Samer; Adam, Adil (New Energy Exploitation and Application, 2026)
Electric switchgear serves as the backbone of any power system; it protects, controls, and isolates electrical circuits. For decades, Sulfur Hexafluoride (SF6) gas has been the insulating and quenching medium of choice. SF6 gas has great dielectric properties, making SF6 gas-insulated switchgear (GIS) compact and highly dependable. However, SF6 gas is highly detrimental to the environment, having a global warming potential of 22,800 times that of CO2. This makes it imperative that SF6 gas be phased out. At the same time, the rapidly developing complexity of power grids has outpaced the time-based maintenance systems. This article provides a summary of key research to examine the important changes that must be made when addressing the phasing out of SF6 gas and the alternatives for medium and high voltage applications. The article also addresses the shift from time-based maintenance to predictive and condition-based maintenance, as well as the impact of advanced analytics, Artificial Intelligence (AI), and Machine Learning (ML) on the future reliability and efficiency of switchgear. The article concludes by highlighting the importance of the emerging patterns and the need for sustainable and resilient electrical systems. Overall, the discussion highlights the need to prepare for innovation in the industry, as well as the need for sustainable and flexible electrical systems. Meeting these challenges will both reduce negative ecological impacts and protect the future viability of the network systems for power distribution.